Pembuatan Sistem Informasi Akuntansi dan Price Calculator Berdasarkan Job Order Costing di Perusahaan Percetakan UD. Kusuma Tirta - Fendy Arya Gunadi; Yulia Yulia; Andy Setiabudi (Jurnal Infra, 2015)
UD.Kusuma Tirta is a company which focused in printing. The company received an order to print receipts, forms, books, brochures, letterhead, business cards, etc. The company has 50-100 transactions in a month, it’s difficult for the company to process the transaction data.Seeing the problems that occur, the solution can be proposed is an accounting information system applications and price calculator to help resolve problems that occur. Application price calculator will help in determining the printing costs. Accounting information system will help company in process transaction data and generate financial reports for the company. This application is made using PHP and use MySQL database.The results to be obtained from applications that have been made is profit income, balance sheet, management report (account payable report, account receiveable report, etc).